2021
DOI: 10.1007/s10143-021-01633-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative red blood cell transfusion is associated with poor functional outcome and overall survival in patients with newly diagnosed glioblastoma

Abstract: The influence of perioperative red blood cell (RBC) transfusion on prognosis of glioblastoma patients continues to be inconclusive. The aim of the present study was to evaluate the association between perioperative blood transfusion (PBT) and overall survival (OS) in patients with newly diagnosed glioblastoma. Between 2013 and 2018, 240 patients with newly diagnosed glioblastoma underwent surgical resection of intracerebral mass lesion at the authors’ institution. PBT was defined as the transfusion of RBC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The fact that the slightest deviation from the standardized treatment protocol (e.g., prolonged mechanical ventilation) might result in a significant loss of lifetime/quality of life is therefore gaining attention [ 13 ]. Thus, it is pertinent to consider not only potential preoperative risk factors but also (adverse) treatment effects in order to be able to adapt clinical assessment/counseling/management of affected patients as well as their relatives [ 15 , 9 , 7 , 16 , 8 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the slightest deviation from the standardized treatment protocol (e.g., prolonged mechanical ventilation) might result in a significant loss of lifetime/quality of life is therefore gaining attention [ 13 ]. Thus, it is pertinent to consider not only potential preoperative risk factors but also (adverse) treatment effects in order to be able to adapt clinical assessment/counseling/management of affected patients as well as their relatives [ 15 , 9 , 7 , 16 , 8 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Control groups were mentioned as "no IOCS use" without further details (n = 1,116) or specified as allogeneic transfusion (n = 16), PAD with or without allogeneic blood (n = 140) or no transfusion necessary (n = 125). logic surgery [1][2][3][4][5][6]. Since a large number of studies of this meta-analysis compared patients treated with IOCS supplemented with allogeneic transfusion to groups of patients not transfused, allogeneic transfused only, or transfused with predonated autologous blood, this design is not appropriate to assess allogeneic transfusion risks.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative allogeneic red blood cell (RBC) transfusion is associated with increased mortality and cancer recurrence in multiple retrospective studies [1][2][3][4][5][6]. The underlying trials adjusted their empirical observations for confounding factors such as preoperative anemia, severity of illness, perioperative blood loss, variations in hemotherapy algorithms, and extent of surgical trauma [7].…”
Section: Introductionmentioning
confidence: 99%
“…Blood donations for transfusion are routinely stored as packed RBC (PRBC) for up to 35 or 42 days, depending on the preservation solution [ 4 ]. In the last decade, many studies have reported the negative outcome of PRBC transfusion in various groups of patients [ 5 , 6 , 7 , 8 , 9 ]. Some studies attributed this to the storage-induced lesion to RBC, while others did not find a correlation with the storage duration [ 6 , 10 , 11 , 12 ].…”
Section: In-vivo and In-vitro Aging Of Rbcmentioning
confidence: 99%